Framework development for improving arrival processing of pilgrims at Hajj and Umrah airport terminals - Abudiyah, Alhussin K. (Cranfield University, 2020)
Millions of Muslims around the world perform the Hajj, a mandatory religious journey to the holy city of Mecca, at least once in their lifetime. Therefore, hundreds of thousands of pilgrims arrive weekly at Jeddah and Medina Airports during the Hajj period determined by the Islamic calendar. Numerous research studies have been published on the health, security, risk management and logistics aspects of the mass gathering. However, studies on pilgrims’ wait times, flow and satisfaction at the Hajj and Umrah Terminals (HT)s are very limited. The research evaluating the inbound passenger domain is especially limited. Therefore, this study contributes to the literature by combining different perspectives regarding the inefficiency of HT processes. Furthermore, this study proposes and investigates various aspects to improve the processing of arriving passengers at HTs. It does so by identifying and studying the factors that impede the flow of passengers within these terminals from users’ and providers’ perspectives. This research aims to contribute by developing an innovative integrated framework to improve the flow of pilgrims through arrival terminals and determining how large crowds at airports can be better managed. To meet the study’s aims, a simulation model is developed to verify and confirm the performance of arrival passenger processes at HTs by conducting a mixedmethods analysis and integrating the numerical results of the agent-based and discrete-event simulation models. This study creates a problematic review matrix based on users’ and providers’ perspectives. In addition, the survey on providers’ perspectives indicates that there are five factors, human, infrastructure, operational, technical and organisational factors, influencing arrival passenger processes at HTs and interacting with level of service (LoS) variables. The study indicates the suboptimal processes at airport terminals to focus on the factors negatively affecting the HT processes. In addition, the research highlights the role of terminal configurations. This study compares two airports in terms of peak demand patterns. According to the study, sharp peaks can have strong negative impacts on HTs, while evenly distributed demand can improve LoS at HTs. The simulation model outcomes verify and confirm the parameters and factors influencing LoS. In addition, the study’s integrated framework provides diverse viewpoints on the operational processes at HTs, while the density map matrix helps to classify the processes. This study applies what-if scenarios to identify the impact of pilgrims’ experience and biometric characteristics and finds that inexperience and certain biometric characteristics have negative impacts on LoS. Limitations of the study and suggestions for future research are discussed.
Keywords: Passenger Flow; Arriving Passenger Processing; Crowded Airports; User’s Perspective; Providers Perspective; Integrated Simulation Model; Level of Service; Hajj And Umrah Airport Terminals